2018
DOI: 10.1136/openhrt-2018-000819
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise therapy on established and emerging circulating biomarkers in patients with heart failure: a systematic review and meta-analysis

Abstract: BackgroundBiomarkers are important in the diagnosis, risk stratification and management of patients with heart failure (HF). The established biomarkers of myocardial stretch, brain natriuretic peptide (BNP) and amino (N) portion of BNP (NT-proBNP) have been extensively studied, and early analyses have demonstrated response to exercise training. Several other biomarkers have been identified over the last decade and may provide valuable and complementary information which may guide treatment strategies, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 97 publications
(172 reference statements)
5
29
0
Order By: Relevance
“…Endothelial biomarkers, ICAM-1, VCAM-1 (68, 69), VEGF (70, 71) were all shown to decrease in patients with cardiovascular risk factors, whereas there was insufficient evidence on the efficacy of exercise on E-selectin. Cardiovascular biomarkers (pro-ADM, pro-ANP) were shown to decrease in patients with heart failure (72, 73), and limited literature is available on the efficacy of exercise on Copeptin. We found only minor changes in the assessed biomarkers without clinical relevance between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial biomarkers, ICAM-1, VCAM-1 (68, 69), VEGF (70, 71) were all shown to decrease in patients with cardiovascular risk factors, whereas there was insufficient evidence on the efficacy of exercise on E-selectin. Cardiovascular biomarkers (pro-ADM, pro-ANP) were shown to decrease in patients with heart failure (72, 73), and limited literature is available on the efficacy of exercise on Copeptin. We found only minor changes in the assessed biomarkers without clinical relevance between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…Our review differs from the two previous systematic reviews which have examined NP levels in non-surgical patients after exercise therapy (Pearson et al 2018; Smart and Steele 2010). These reviews also found that NP levels were reduced after exercise therapy, with a high heterogeneity in the response.…”
Section: Discussionmentioning
confidence: 87%
“…These reviews also found that NP levels were reduced after exercise therapy, with a high heterogeneity in the response. The strength of our review is that it updates the previous reviews (Smart and Steele 2010) with more trials and only includes RCTs with aerobic exercise programmes (Pearson et al 2018). We did not consider trials examining yoga, stretching, Tai chi, functional electrical stimulation, or inspiratory muscle training (Pearson et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In adults with CVD without cancer, exercise training is recognized as an important approach in cardiac rehabilitation [16]. Particularly, two meta-analyses have shown favorable effects of exercise on attenuation of N-terminal pro-brain natriuretic peptide (NT-proBNP) [17] and mitigation of LV remodeling [18] in patients with heart failure. Also, in the oncological setting, it has become clear that exercise is a safe and effective supportive therapy in the management of several treatment-related side effects and in improving overall physical fitness [19, 20].…”
Section: Introductionmentioning
confidence: 99%